Pregnancy and Exercise in Mountain Travelers. Issue 3 (March 2023) - Keyes, Linda E.; Sanders, Linda
Abstract : In uncomplicated pregnancies, short visits to high altitude are probably safe, and restricting travel and activities may have unnecessary negative consequences. Abstract: Pregnant women are traveling to high altitude and evidence-based recommendations are needed. Yet, there are limited data regarding the safety of short-term prenatal high-altitude exposure. There are benefits to prenatal exercise and may be benefits to altitude exposure. Studies evaluating maternofetal responses to exercise at altitude found the only complication was transient fetal bradycardia, a finding of questionable significance. There are no published cases of acute mountain sickness in pregnant women, and data suggesting an increase in preterm labor are of poor quality. Current recommendations across professional societies are overly cautious and inconsistent. Non-evidence-based restrictions to altitude exposure can have negative consequences for a pregnant women's physical, social, mental, and economic health. Available data suggest that risks of prenatal travel to altitude are low. Altitude exposure is likely safe for women with uncomplicated pregnancies. We do not recommend absolute restrictions to high altitude exposure, but rather caution and close self-monitoring.